2017
DOI: 10.1371/journal.pone.0168847
|View full text |Cite
|
Sign up to set email alerts
|

A Blind Spot? Screening for Mild Intellectual Disability and Borderline Intellectual Functioning in Admitted Psychiatric Patients: Prevalence and Associations with Coercive Measures

Abstract: BackgroundFailure to detect psychiatric patients’ intellectual disabilities may lead to inappropriate treatment and greater use of coercive measures.AimsIn this prospective dynamic cohort study we screened for intellectual disabilities in patients admitted to psychiatric wards, and investigated the use of coercive measures with these patients.MethodsWe used the Screener for Intelligence and Learning disabilities (SCIL) to screen patients admitted to two acute psychiatric wards, and assessed patient characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…As can be seen, the SCIL results suggested that 20% of the patients had MID and 20% had BIF, resulting in a total of 40% of the patients being suspected to have MBID as indicated by a SCIL score of ≤19. In comparison, it was found that 43.8% of the patients scored ≤19 on the SCIL in the earlier study by Nieuwenhuis et al () among acutely admitted psychiatric patients. Results of the regular IQ tests suggested that over half of the patients were functioning on the level of MBID, as 58% had an IQ of 84 or lower, and one out of five patients (20%) might have had MID (see Figure ).…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…As can be seen, the SCIL results suggested that 20% of the patients had MID and 20% had BIF, resulting in a total of 40% of the patients being suspected to have MBID as indicated by a SCIL score of ≤19. In comparison, it was found that 43.8% of the patients scored ≤19 on the SCIL in the earlier study by Nieuwenhuis et al () among acutely admitted psychiatric patients. Results of the regular IQ tests suggested that over half of the patients were functioning on the level of MBID, as 58% had an IQ of 84 or lower, and one out of five patients (20%) might have had MID (see Figure ).…”
Section: Resultsmentioning
confidence: 65%
“…In this article, we will address these two groups together (i.e., patients with MID and BIF) by using MBID as an umbrella term. Based on the results of Nieuwenhuis et al (), the prevalence of (suspected) MBID among hospitalized psychiatric patients clearly appears to be elevated. On the basis of a normal distribution, one may expect that about 16% of the general population has an IQ below 85.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations